Innovative Learning Strategies to Increase Students’ Participation and Quality of English Teaching and Learning Process - Ampa, Andi Tenri; Nurqalbi, Nurqalbi (Technium Social Sciences Journal, 2021)
Abstract: One of the factors that may influence the success of the teaching and learning process is to use appropriate and innovative strategies of both online and offline. Therefore, the study aimed to describe the extent to which the lecturers of the English education department at Faculty of Teachers Training and Education, Unismuh Makassar apply innovative learning strategies to increase the students’ participation and the quality of the teaching and learning process. The study used a 'mixed method', namely by obtaining quantitative and qualitative data. The research subjects were lecturers of the English language education department with the criteria that they had obtained an educator certificate. The research instrument used a questionnaire to answer the problems and to achieve research objectives. Data analysis was performed using descriptive statistics. The results showed that the innovative teaching strategies used by the lecturers were cross over teaching, teaching through smart boards, flipping classrooms, collaboration, virtual reality, cloud computing, inquiry-based teaching and problem-based learning.